The Influence of ESG Performance, Asset Productivity, Financial Risk, and Market Valuation on Financial Performance - Aisyah Sayidul Lintang Wiharyono; Dewi Riza Lisvi Vahlevi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the impact of Sustainability (ESG Score), Asset Productivity (TATO), Financial Risk (DER), and Market Valuation (PBV) on Financial Performance (ROA). The study subjects were 20 dual-listed companies listed on ISSI and ESG Sector Leaders (IDX-KEHATI) (60 observations, 2022–2024). Using panel data regression analysis, the results show that TATO and PBV have a significant positive effect on ROA, highlighting the importance of operational efficiency and market prospects in improving profitability. Conversely, DER and ESG have a significant negative effect on ROA. The negative influence of ESG implies a trade-off between short-term compliance costs, which depress net income. Conclusively, operational fundamentals (TATO and PBV) are the most dominant determinants of financial performance (ROA). These findings have implications for the formulation of future Sharia-ESG Index criteria, recommending a high TATO filter, positive PBV, and low DER to select issuers with superior bottom-line and sustainable performance.